Role of Matricellular CCN Proteins in Skeletal Muscle: Focus on CCN2/CTGF and Its Regulation by Vasoactive Peptides - Rebolledo, Daniela L.; Acuna, Maria Jose; Brandan, Enrique (My University, 2021)
The Cellular Communication Network (CCN) family of matricellular proteins comprises six proteins that share conserved structural features and play numerous biological roles. These proteins can interact with several receptors or soluble proteins, regulating cell signaling pathways in various tissues under physiological and pathological conditions. In the skeletal muscle of mammals, most of the six CCN family members are expressed during embryonic development or in adulthood. Their roles during the adult stage are related to the regulation of muscle mass and regeneration, maintaining vascularization, and the modulation of skeletal muscle fibrosis. This work reviews the CCNs proteins' role in skeletal muscle physiology and disease, focusing on skeletal muscle fibrosis and its regulation by Connective Tissue Growth factor (CCN2/CTGF). Furthermore, we review evidence on the modulation of fibrosis and CCN2/CTGF by the renin-angiotensin system and the kallikrein-kinin system of vasoactive peptides.
Keywords: cellular communication network; ccn; skeletal muscle; vasoactive peptides; fibrosis; ccn2; ctgf; kks